Analysis of Learning Media Financing Management Based on Islamic Economic Principles at SMP Rahmat Islamiyah Medan - Hasrian Rudi Setiawan; Isman Efendi Limbong; Fitri Hayati (Al-Sharf: Jurnal Ekonomi Islam, 2026)
This study aims to analyze the management of learning media financing based on Islamic economic principles at SMP Rahmat Islamiyah Medan. Effective learning requires adequate media support, the procurement of which heavily relies on proper financial management. This research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observations, and documentation involving school administrators, treasurers, and teachers. The results indicate that the planning, allocation, and supervision of the learning media financing budget at SMP Rahmat Islamiyah Medan generally incorporate Islamic economic values, such as the principles of justice (fairness), trust/amanah (transparency and accountability), efficiency (avoiding waste/israf), and halallness in both sources and utilization. However, several technical challenges remain regarding the optimization of sustainable fund allocation. In conclusion, applying financing management based on Islamic economic principles effectively enhances the procurement of learning media while ensuring the integrity and blessing of the school's financial governance.